Winning in turbulence - Rigby, Darrell (Boston, Mass. ; London : Harvard Business Press / McGraw-Hill, 2009)
The current downturn may prove more brutal than most previous recessions. But downturns present strategic opportunities, too. This volume explains how to diagnose your situation and then craft an action plan tailored to the situation you've diagnosed.
BSBA
Keywords: Success in business; Management; Financial crises -- History -- 21st century